The Nature and Extent of English Lexical Borrowings into Bangla: An Investigation into selected Modern Bengali Novels and Short Stories - Muhammad Azizul Hoque; Dr. Fariza Puteh Behak; Dr. Hazleena Baharun; Dr Rafqul Islam Molla (International Journal of English Language and Translation Studies, 2018)
English lexical borrowings are a common manifestation in Bangla. Modern Bengali literary texts like novels and short stories, likewise, display a wide range of English lexis. The observation of the phenomenon has motivated the present researchers to move forward with the study of five modern Bengali novels and five short stories in order to explore the borrowings in a variety of natures and extents and their consequent impact on Bangla. After a careful collection of English borrowings from the texts, the borrowings have been categorized as with Bengali equivalents, without Bengali equivalents, with close Bengali equivalents and hybridized. The findings show the depth and breadth of English lexis with about 65% English lexis with Bengali equivalents, 19% without Bengali equivalents, 13% with close Bengali equivalents and 4% hybridized observed in several domains. The phenomena show their consequent impact on Bangla. As a result, it is believed that many English loans are gradually getting integrated into Bangla. In many cases, they are additions to Bengali lexical stock, but in many other cases they are replacing Bengali equivalents. It is feared that replacement of Bengali lexis by the English counterparts may contribute to shifting of them. Thereby, this phenomenon may produce mixed impacts-lexically both enriching and impoverishing Bangla. Methodologically, the present research is based on a qualitative content analysis under a descriptive framework. Finally, the study likes to recommend finding ways to guide English borrowings, specifically for enriching and safeguarding the rich heritage of Bangla, particularly in literary texts like novels and short stories in Bangladesh.